1995
DOI: 10.1021/bi00026a002
|View full text |Cite
|
Sign up to set email alerts
|

The D-Helix in Myoglobin and in the .beta. Subunit of Hemoglobin Is Required for the Retention of Heme

Abstract: All globins consist of eight helices and interconnecting loops except alpha hemoglobin subunits which lack the D-helix due to deletion of five consecutive residues. Previous site-directed mutagenesis work suggested that this deletion is a neutral modification in hemoglobin with respect to equilibrium O2 binding [Komiyama, N. H., Shih, T.-B., Looker, D., Tame, J., & Nagai, K. (1991) Nature 352, 349-351]. To examine the role of the D-helix in myoglobin, we have measured the O2 and CO binding and hemin dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…Noncovalent heme-binding proteins such as myoglobin (Mb) and hemoglobin (Hb) have been extensively studied in solution [30][31][32][33][34][35][36][37][38][39][40][41][42] as well as in the gas phase [3][4][5][6][7][8]10,11,43]. In solution, the binding of ligands such as O 2 and CO [30,38,39], and the affinity of the protein for the heme group, have been studied [30][31][32][33][34][35][40][41][42] In gas-phase studies, McLuckey and Ramsey [7] reported that holo-Mb ions could be trapped for 1 s in a quadrupole ion trap mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noncovalent heme-binding proteins such as myoglobin (Mb) and hemoglobin (Hb) have been extensively studied in solution [30][31][32][33][34][35][36][37][38][39][40][41][42] as well as in the gas phase [3][4][5][6][7][8]10,11,43]. In solution, the binding of ligands such as O 2 and CO [30,38,39], and the affinity of the protein for the heme group, have been studied [30][31][32][33][34][35][40][41][42] In gas-phase studies, McLuckey and Ramsey [7] reported that holo-Mb ions could be trapped for 1 s in a quadrupole ion trap mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…In solution, the binding of ligands such as O 2 and CO [30,38,39], and the affinity of the protein for the heme group, have been studied [30][31][32][33][34][35][40][41][42] In gas-phase studies, McLuckey and Ramsey [7] reported that holo-Mb ions could be trapped for 1 s in a quadrupole ion trap mass spectrometer. Dissociation of the 9 + charge state resulted in the production of singly charged heme and the 8 + charge state of the protein [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each hemoglobin molecule contains 2 alpha chains and 2 beta chains, subunits which are identifiable by structural characteristics [13]. Alpha hemoglobins lack a specific alpha-helix, the D helix, that is present in beta hemoglobins [14]. Many organisms have several distinct hemoglobins, an adult form and embryonic or fetal forms created by combining different alpha and beta hemoglobin units [13].…”
Section: Resultsmentioning
confidence: 99%
“…One b-turn is around a50 and a51, and the other is around a71 and a72. Amino acids in the two regions have (Whitaker et al 1995) an important role in Hb transformation (Srinivasan and Rose 1994). The second and third d N /d S peaks in bats are located in the two b-turns, and the changes apparent in bats may be involved in Hb transformation.…”
Section: Discussionmentioning
confidence: 99%